KORELASI ANTARA BERAT LAHIR DAN POLA ASUH PADA BALITA USIA 24 – 60 BULAN DENGAN KEJADIAN STUNTING DI BANJARNEGARA - Dian Nirmala (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2022)
The incidence of stunting (short) toddlers is a major nutritional problem faced by Indonesia. Based on the Nutritional Status Monitoring (PSG) data for the last three years, stunting has the highest prevalence compared to other nutritional problems such as undernutrition, thinness, and obesity. Factors that influence the history of LBW and upbringing. The purpose of the study was to determine the relationship between LBW and parenting with the incidence of stunting. The research method is quantitative with a case control approach. The sample in this study were toddlers aged 2-5 years. The results of the chi square test showed that there was a relationship between birth weight and the incidence of stunting under five (p value 0.000), there was no relationship between parenting and the incidence of stunting under five (p value 0.106). Suggestions for health workers in carrying out midwifery care, especially for patients with a history of LBW, to do care as early as possible so that the baby's growth is normal and suppresses the incidence of stunting.